Is enamel the only reliable hard tissue for sex metric estimation of burned skeletal remains in biological anthropology? - Godinho, Ricardo Miguel (2019)
Sex diagnosis is a crucial element in the analysis of skeletal remains from forensic and archaeological contexts. Thus, researchers have developed several methods using different anatomical regions to estimate sex. Despite such variety of methods, sexing of collective cremated human skeletal remains is still challenging due to heat-induced size changes and fragmentation, along with the typical commingling of collective contexts. This study aims to examine the potential of burned tooth crowns for odontometric sex estimation. To that end, heat-induced size changes were quantified in experimentally heated teeth. Then, odontometric sex estimation was performed in a set of theoretical samples of pre and post-heated tooth crowns. Results show heated tooth crowns undergo variable but consistent and statistically significant expansion, which is due to micro-fracturing. Such heat induced size changes are of sufficient magnitude to impact odontometric sex diagnosis and sex ratios of the theoretical samples. Yet, sexing using heated/burned tooth crowns may still be useful to estimate the minimum number of females in a given sample. Further, the effect of heat-induced size changes may be calculated and removed using mu CT scanning.